Biochemical comparison of two Hypostomus populations (Siluriformes, Loricariidae) from the Atlântico Stream of the upper Paraná River basin, Brazil - Kennya F. Ito (Genetics and Molecular Biology, 2009)
Two syntopic morphotypes of the genus Hypostomus - H. nigromaculatus and H. cf. nigromaculatus (Atlântico Stream, Paraná State) - were compared through the allozyme electrophoresis technique. Twelve enzymatic systems (AAT, ADH, EST, GCDH, G3PDH, GPI, IDH, LDH, MDH, ME, PGM and SOD) were analyzed, attributing the score of 20 loci, with a total of 30 alleles. Six loci were diagnostic (Aat-2, Gcdh-1, Gpi-A, Idh-1, Ldh-A and Mdh-A), indicating the presence of interjacent reproductive isolation. The occurrence of few polymorphic loci acknowledge two morphotypes, with heterozygosity values He = 0.0291 for H. nigromaculatus and He = 0.0346 for H. cf. nigromaculatus. F IS statistics demonstrated fixation of the alleles in the two morphotypes. Genetic identity (I) and distance (D) of Nei (1978) values were I = 0.6515 and D = 0.4285. The data indicate that these two morphotypes from the Atlântico Stream belong to different species.